2019
DOI: 10.3389/fendo.2019.00840
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNAs in the Regulation of Subcutaneous White Adipose Tissue in Individuals With Obesity and Without Type 2 Diabetes

Abstract: Obesity is a high-risk factor for such comorbidities as cardiovascular disease, several types of cancer, and type 2 diabetes; however not all individuals with obesity have such complications. Approximately 20% of individuals with obesity are metabolically healthy. This study focused on differences between obese individuals with and without type 2 diabetes (T2D+ and T2D–, respectively) on the transcriptome level. Subjects included were 35 T2D– patients with obesity and 35 T2D+ patients with obesity with the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
(43 reference statements)
2
20
0
1
Order By: Relevance
“…Upregulation of top DE miRNAs in VAT of hyperglycemic patients stays in line with studies evaluating expression changes of miR-125b-5p, miR-199a-3p, let-7d-5p and let-7e-5p upon HG or in serum and tissues of T2DM patients or animal models of diabetes [ 28 , 29 , 30 , 31 ]. miR-365a-3p was found to be most highly correlated, along with miR-125b-5p, with HbA1c in serum of type 1 diabetic subjects [ 32 ], similarly to our data.…”
Section: Discussionsupporting
confidence: 76%
“…Upregulation of top DE miRNAs in VAT of hyperglycemic patients stays in line with studies evaluating expression changes of miR-125b-5p, miR-199a-3p, let-7d-5p and let-7e-5p upon HG or in serum and tissues of T2DM patients or animal models of diabetes [ 28 , 29 , 30 , 31 ]. miR-365a-3p was found to be most highly correlated, along with miR-125b-5p, with HbA1c in serum of type 1 diabetic subjects [ 32 ], similarly to our data.…”
Section: Discussionsupporting
confidence: 76%
“…MiR-23b plays important roles in cell growth and differentiation during development [ 6 ], cancer [ 7 ], cardiovascular disease [ 8 ], viral infections [ 9 ], and autoimmune diseases [ 10 ]. In addition, the miR-23b level was reduced in T2D patients with obesity [ 11 ]. Other results indicated that miR-23b and miR-27b were downregulated in muscle stem cells derived from T2DM patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three miRNAs are interesting-miR-1, miR-155 and miR-204. These miRNAs are connected with proliferation, apoptosis, and cardiac injury [25] as well as transforming growth factor-β1 (TGF-β1) and glial cell line-derived neurotrophic factor (GDNF) regulation during glaucoma, asthma and obesity [26][27][28][29]. However, what is even more interesting is that it has been also shown that these miRNAs regulate brain-derived neurotrophic factor (BDNF) [30][31][32].…”
Section: Discussionmentioning
confidence: 99%